Porous polymer microsphere as well as preparation method and application thereof

By coating porous polymer microspheres on the battery separator, the problem of poor bonding between the separator and the pole sheet is solved, efficient bonding at room temperature is achieved, production costs and safety risks are reduced, and the energy density and cycle life of the battery are improved.

CN119570102APending Publication Date: 2025-03-07WUHAN ZHONGXING INNOVATIVE MATERIAL TECHNOLOGIES CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411632317.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the prior art, the bonding effect between the diaphragm and the pole sheet is poor, resulting in battery interface problems, such as increased interface impedance, decreased battery capacity and shortened cycle life. Traditional methods require hot pressing at high temperatures, increasing production costs and safety risks.

Method used

Porous polymer microspheres are used, which are composed of secondary particles and a cladding layer. The secondary particles are porous mesh structures formed by polymerization of polyvinylidene fluoride-based polymers. The cladding layer is a polyacrylic polymer. By coating the microspheres on the separator, the bonding between the separator and the electrode sheet is achieved.

Benefits of technology

The bonding effect between the diaphragm and the pole sheet is improved, so that the diaphragm and the pole sheet can be bonded at room temperature, reducing production costs and safety risks, and improving the energy density and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570102A_ABST
    Figure CN119570102A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery diaphragms, in particular to a porous polymer microsphere and a preparation method and application thereof.The porous polymer microsphere is internally provided with a porous structure and comprises secondary particles and a coating layer coating the surfaces of the secondary particles, and the secondary particles are of a porous grid structure formed by polymerizing primary particles; the primary particles comprise a polyvinylidene fluoride polymer, and the coating layer comprises a polyacrylic acid polymer. The secondary particles have abundant pores, so that the liquid absorption and retention performance of the diaphragm can be improved, and meanwhile, the diaphragm has a relatively high compression ratio and is beneficial to improving the energy density of the battery. Compared with the polyacrylic acid polymer, the polyvinylidene fluoride polymer has higher crystallinity, and the polyacrylic acid polymer coats the surface of the secondary particle composed of the polyvinylidene fluoride polymer, so that the overall crystallinity of the porous polymer microsphere can be improved, and the adhesive property of the porous polymer microsphere is improved; and the bonding effect between the diaphragm and the pole piece can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery separators, and more specifically to a porous polymer microsphere and a preparation method and application thereof. Background Art

[0002] In the field of secondary battery technology, especially lithium-ion batteries, the diaphragm is a key component, which plays the role of isolating the positive and negative electrodes, preventing short circuits, and allowing ions to pass through, thereby achieving normal operation of the battery. However, the bonding effect between the diaphragm and the pole piece has an important influence on the performance of the battery. If the bonding between the diaphragm and the pole piece is not strong, it may cause battery interface problems, such as increased interface impedance, decreased battery capacity, and shortened cycle life. Therefore, how to improve the bonding effect between the diaphragm and the pole piece has become one of the important research directions in the field of battery manufacturing. The traditional method is to coat the surface of the base film with a polymer coating to enhance the bonding force between the diaphragm and the pole piece. However, the traditional polymer coating needs to be hot-pressed at high temperature to achieve bonding with the pole piece, which not only increases the production cost, but also increases the safety risks in the production process.

[0003] Therefore, how to improve the bonding effect between the diaphragm and the electrode is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0004] The present application provides a porous polymer microsphere and a preparation method and application thereof, which can effectively improve the bonding effect between the electrode and the diaphragm, and achieve bonding between the two at room temperature.

[0005] The present application provides a porous polymer microsphere, wherein the porous polymer microsphere has a porous structure inside, including secondary particles and a coating layer coated on the surface of the secondary particles, wherein the secondary particles are a porous grid structure formed by polymerization of primary particles, the primary particles include polyvinylidene fluoride polymers, and the coating layer includes polyacrylic acid polymers.

[0006] In an optional embodiment, the coating layer is discontinuously coated on the surface of the secondary particles.

[0007] In an optional embodiment, the coating layer is continuously coated on the surface of the secondary particles.

[0008] In an optional embodiment, the porous polymer microspheres satisfy at least one of the conditions (1)-(6):

[0009] (1) The particle size of the porous polymer microspheres is 1 μm-10 μm;

[0010] (2) In the porous polymer microspheres, the mass ratio of the polyvinylidene fluoride polymer to the polyacrylic acid polymer is 2:1-20:1;

[0011] (3) The polyvinylidene fluoride polymer includes at least one of a polyvinylidene fluoride homopolymer, a polyvinylidene fluoride-trifluoroethylene copolymer and a polyvinylidene fluoride-hexafluoropropylene copolymer;

[0012] (4) The melting point of the polyvinylidene fluoride polymer is 80°C-150°C;

[0013] (5) The particle size of the primary particles is 80nm-400nm;

[0014] (6) The polyacrylic acid polymer comprises a polymer composed of at least one monomer selected from acrylic acid, acrylic ester, acrylonitrile and acrylamide;

[0015] Optionally, the polyacrylic acid polymer is polymethyl methacrylate.

[0016] The present application provides a method for preparing the above-mentioned porous polymer microspheres, the steps of which include:

[0017] The primary particles are mixed with a surfactant to prepare secondary particles having a porous grid structure;

[0018] Mixing a solvent, an emulsifier and the secondary particles to form a secondary particle emulsion;

[0019] Mixing a solvent, an emulsifier and a monomer for preparing a coating layer to form a coating layer emulsion;

[0020] The secondary particle emulsion, the coating layer emulsion and the initiator are mixed and heated for reaction, so that the prepared monomers are polymerized on the surface of the secondary particles to form the coating layer, thereby preparing porous polymer microspheres.

[0021] In an optional embodiment, the porous polymer microspheres are prepared by satisfying at least one of the following conditions (1) to (5):

[0022] (1) The surfactant comprises at least one of fluoroalkyl methoxy ether alcohol, fluoroalkyl ethoxy ether alcohol, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, polyvinyl alcohol, fatty acid polyoxyethylene ether and polyoxyethylene;

[0023] (2) In the step of preparing the secondary particles, the mass ratio of the primary particle raw material to the surfactant is 100:0.1-100:2;

[0024] (3) In the preparation of the secondary particle emulsion, the mass percentage of the secondary particles is 15%-30%; the mass percentage of the emulsifier is 0.1%-2%;

[0025] (4) In the preparation of the coating layer emulsion, the mass percentage of the emulsifier is 0.1%-2%;

[0026] (5) The temperature of the heating reaction is 75°C-90°C.

[0027] In an optional embodiment, a drying and dehydration treatment is further included after the heating reaction to obtain dry porous polymer microspheres, and the drying and dehydration treatment includes vacuum drying or spray drying.

[0028] The present application provides a membrane coating slurry, comprising the porous polymer microspheres as described above or the porous polymer microspheres prepared by the preparation method as described above.

[0029] In an optional embodiment, the membrane coating slurry satisfies at least one of the conditions (1)-(2):

[0030] (1) In the membrane coating slurry, the mass percentage of the porous polymer microspheres is 8%-20%;

[0031] (2) The solid content of the diaphragm coating slurry is 10%-20%.

[0032] The present application provides a separator, comprising the porous polymer microspheres as described above or the porous polymer microspheres prepared by the preparation method as described above.

[0033] According to the porous polymer microspheres in the above-mentioned embodiment, the porous polymer microspheres have a porous structure inside, including secondary particles and a coating layer coated on the surface of the secondary particles, the secondary particles are a porous grid structure formed by the polymerization of primary particles, the primary particles include polyvinylidene fluoride polymers, and the coating layer includes polyacrylic acid polymers. Since the secondary particles serving as the skeleton and the core layer are formed by the aggregation of a plurality of primary particles including polyvinylidene fluoride polymers, and a coating layer composed of polyacrylic acid polymers is arranged on the surface of the secondary particles, the secondary particles have abundant pores, which can improve the liquid absorption and retention performance of the diaphragm, and the porous grid structure formed at the same time has a large compression rate. When applied to the diaphragm, the thickness of the compressed diaphragm increases less than that of the porous substrate layer, which is beneficial to improving the energy density of the battery. Since polyvinylidene fluoride polymers have higher crystallinity and higher hardness than polyacrylic acid polymers, polyacrylic acid polymers are coated on the surface of secondary particles composed of polyvinylidene fluoride polymers to form a hard-core-soft-shell structure. Compared with uncoated polyvinylidene fluoride polymers, the overall crystallinity of the porous polymer microspheres can be improved, thereby improving the bonding properties of the porous polymer microspheres. Applying it in the diaphragm can improve the bonding effect between the diaphragm and the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1A schematic diagram of the structure of porous polymer microspheres in an embodiment;

[0035] Figure 2 is a scanning electron microscope image of primary particles in one embodiment;

[0036] Figure 3 A schematic diagram of the preparation process of porous polymer microspheres in an embodiment;

[0037] Figure 4 A schematic diagram of the preparation process of porous polymer microspheres in another embodiment;

[0038] Figure 5 is a scanning electron microscope image of the diaphragm in Example 1;

[0039] Figure 6 This is a scanning electron microscope image of the diaphragm in comparative example 1.

[0040] Among them: 100, primary particles; 200, coating layer. DETAILED DESCRIPTION

[0041] The present application is further described in detail below by specific embodiments in conjunction with the accompanying drawings. Wherein similar elements in different embodiments adopt associated similar element numbers. In the following embodiments, many detailed descriptions are intended to enable the present application to be better understood. However, those skilled in the art can easily recognize that some of the features can be omitted in different situations, or can be replaced by other elements, materials, and methods. In some cases, some operations related to the present application are not shown or described in the specification, in order to avoid the core part of the present application being overwhelmed by too much description, and for those skilled in the art, it is not necessary to describe these related operations in detail, and they can fully understand the related operations based on the description in the specification and the general technical knowledge in the art.

[0042] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various implementations, and the operation steps involved in each embodiment can also be replaced or adjusted in a sequence in a manner that is obvious to those skilled in the art. Therefore, the specification and drawings are only for the purpose of clearly describing a certain embodiment and do not mean that the composition and / or sequence are necessary.

[0043] The serial numbers of the components in this document, such as "first", "second", etc., are only used to distinguish the objects described and do not have any order or technical meaning. The "connection" and "coupling" mentioned in this application, unless otherwise specified, include direct and indirect connections (couplings).

[0044] Secondary batteries refer to batteries that can be used again by recharging the active materials after the battery is discharged. This type of battery usually uses the reversibility of chemical reactions, that is, after a chemical reaction is converted into electrical energy, the chemical system can be repaired with electrical energy, and then converted into electrical energy by chemical reaction again. Among them, the more common secondary batteries include but are not limited to nickel-metal hydride batteries, nickel-cadmium batteries, lead-acid (or lead storage) batteries, lithium-ion batteries, polymer lithium-ion batteries, sodium-ion batteries, etc.

[0045] In this application, the so-called "diaphragm" is an important component of the secondary battery cell. The diaphragm is a thin film used to separate the positive and negative electrodes during the electrolysis reaction to prevent the loss of energy in the direct reaction. The performance of the diaphragm determines the interface structure and internal resistance of the battery, and directly affects the battery's capacity, cycle and safety performance. A diaphragm with excellent performance plays an important role in improving the overall performance of the battery.

[0046] At the same time, since the diaphragm is bonded to the positive and negative electrodes in the battery, the diaphragm and the positive and negative electrodes support each other to form a battery with a certain thickness and hardness. When the battery is working, the negative electrode will expand during the charging and discharging process. If the bonding force is weak, a gap will form between the positive and negative electrode sheets and the diaphragm. The positive and negative electrode sheets and the diaphragm cannot fit together and support each other, resulting in a loose battery and a lower hardness. At this time, the power performance of the battery will deteriorate, for example, the rate performance will be reduced, and at the same time, the cycle performance will deteriorate.

[0047] In the traditional solution, a polymer coating is applied on the surface of the diaphragm to improve the adhesion between the diaphragm and the positive and negative electrodes. However, the polymer coating needs to be hot-pressed at high temperature to achieve adhesion with the electrode, which increases the production cost of the manufacturer and also increases the cost for consumers.

[0048] Based on the above problems, the present application provides a porous polymer microsphere that can be used to prepare a functional coating of a diaphragm to enhance the bonding effect between the diaphragm and the pole piece and achieve bonding between the diaphragm and the pole piece at room temperature.

[0049] See also Figure 1 to Figure 2 The porous polymer microsphere has a porous structure inside, including secondary particles and a coating layer 200 coated on the surface of the secondary particles. The secondary particles are a porous grid structure formed by polymerization of primary particles 100. The primary particles 100 include polyvinylidene fluoride polymers, and the coating layer 200 includes polyacrylic acid polymers.

[0050] The present application creatively utilizes a plurality of primary particles 100 to polymerize to form secondary particles of a porous grid structure, and then uses the secondary particles as a skeleton and a core layer, and arranges a coating layer 200 composed of a polyacrylic acid polymer on its surface, and the secondary particles composed of the primary particles 100 have abundant pores, which can improve the liquid absorption and liquid retention performance of the diaphragm, and the porous grid structure composed at the same time has a large compression rate. When applied to the diaphragm, the thickness of the compressed diaphragm is increased less than that of the porous substrate layer, which is beneficial to improving the energy density of the battery. Since the polyvinylidene fluoride polymer has a higher crystallinity than the polyacrylic acid polymer and has a higher hardness, the polyacrylic acid polymer is coated on the surface of the secondary particles composed of the polyvinylidene fluoride polymer, so that a hard-core soft-shell structure is formed, which can improve the overall crystallinity of the porous polymer microspheres (reduced crystallinity) compared to the uncoated polyvinylidene fluoride polymers, thereby improving the bonding performance of the porous polymer microspheres, and applying it in the diaphragm can improve the bonding effect between the diaphragm and the pole piece.

[0051] It should be noted that crystallinity is used to indicate the proportion of crystalline regions in a polymer. Crystallinity is an orderly arrangement of molecular chains. Polymers with high crystallinity have more regular molecular chains and stronger intermolecular forces, which may lead to reduced bonding strength. Therefore, reducing crystallinity is beneficial to improving the bonding performance of polymers.

[0052] In some embodiments, see Figure 1 , the coating layer 200 is non-continuously coated on the surface of the secondary particles. Specifically, the coating layer 200 can be understood to be composed of a plurality of coating units, and there are gaps between the plurality of coating units. The secondary particles can be exposed at the position of the gaps. Since the polyvinylidene fluoride polymer has good bonding properties, the bonding properties of the porous polymer microspheres can be effectively guaranteed, and the specific surface area of ​​the entire porous polymer microspheres can be increased, so that the coating layer 200 can play a greater bonding role.

[0053] Of course, in other embodiments, the coating layer 200 may also be continuously coated on the surface of the secondary particles. Specifically, the coating layer 200 may be understood as an integral structure that fully covers the surface of the secondary particles, which may improve the aggregation tightness between the primary particles 100 constituting the secondary particles, thereby improving the mechanical strength of the porous polymer microspheres and the mechanical strength of the diaphragm.

[0054] In some embodiments, the particle size of the porous polymer microspheres is 1 μm-10 μm. For example, the particle size of the porous polymer microspheres is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm. The use of porous polymer microspheres in the above particle size range will not affect the thickness of the diaphragm, which is conducive to the thinning of the diaphragm, and will not block the ion channel, thereby effectively ensuring the transmission of ions.

[0055] It should be understood that when the particle size of the diaphragm coating is too large, a thicker coating will be formed on the diaphragm, affecting the energy density of the produced battery. When the particle size of the diaphragm coating is too small, it is easy to block the pore structure on the diaphragm, thereby affecting the passage of ions in the diaphragm and affecting the transmission of ions.

[0056] In some embodiments, in the porous polymer microspheres, the mass ratio of the polyvinylidene fluoride polymer to the polyacrylic acid polymer is 2:1-20:1. For example, the mass ratio of the polyvinylidene fluoride polymer to the polyacrylic acid polymer is 2:1, 3:1, 5:1, 8:1, 10:1, 12:1, 15:1 or 20:1, or within the range of any two of the above values. Optionally, the mass ratio of the polyvinylidene fluoride polymer to the polyacrylic acid polymer is 5:1-10:1. When the mass ratio of the polyvinylidene fluoride polymer to the polyacrylic acid polymer is set within the above range, the pores in the secondary particles will not be blocked due to excessive use of the polyacrylic acid polymer, thereby affecting the porosity of the diaphragm, nor will the adhesion of the porous polymer microspheres be insufficient due to insufficient use of the polyacrylic acid polymer, thereby affecting the adhesion effect of the diaphragm and the electrode.

[0057] In some embodiments, the polyvinylidene fluoride-based polymer includes at least one of polyvinylidene fluoride homopolymer (PVDF), polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TFE), and polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP).

[0058] In some embodiments, the melting point of the polyvinylidene fluoride polymer is 80°C-150°C. For example, the melting point of the polyvinylidene fluoride polymer is 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, or in the range of any two of the above values. The polyvinylidene fluoride polymer with a low melting point is selected, which has good adhesion at room temperature, so that the porous polymer microspheres can also have good adhesion at room temperature, which helps to achieve the adhesion of the diaphragm and the electrode at room temperature.

[0059] See also Figure 2 In some embodiments, the particle size of the primary particle 100 is 80 nm-400 nm. For example, the particle size of the primary particle 100 is 80 nm, 90 nm, 100 nm, 200 nm, 300 nm or 400 nm, or within the range of any two of the above values.

[0060] In some embodiments, the polyacrylic acid polymer comprises a polymer composed of at least one monomer selected from acrylic acid, acrylic acid ester, acrylonitrile and acrylamide. Preferably, the polyacrylic acid polymer is polymethyl methacrylate (PMMA).

[0061] See also Figure 3 The present application also provides a method for preparing the porous polymer microspheres, the steps of which include:

[0062] S101: mixing the primary particles 100 and a surfactant to prepare secondary particles having a porous grid structure.

[0063] Specifically, when preparing secondary particles, the surfactant includes at least one of fluoroalkyl methoxy ether alcohol, fluoroalkyl ethoxy ether alcohol, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, polyvinyl alcohol, fatty acid polyoxyethylene ether and polyoxyethylene. The polyvinylidene fluoride polymer and the surfactant of the primary particle 100 are mixed according to a ratio and mechanically stirred, and the polymer particles are granulated by mechanical stirring, so that the surfactant is dispersed between multiple polyvinylidene fluoride polymer particles, and multiple polyvinylidene fluoride polymer particles are agglomerated to form a secondary particle structure with a porous grid structure. The mass ratio of the raw material of the primary particle 100 and the surfactant is 100:0.1-100:2. For example, the mass ratio of the raw material of the primary particle 100 and the surfactant is 100:0.1, 100:0.5, 100:1, 100:1.1, 100:1.5 or 100:2, or within the range of any two of the above values.

[0064] S102, mixing the solvent, the emulsifier and the secondary particles to form a secondary particle emulsion.

[0065] Specifically, a solvent, an emulsifier and secondary particles are mixed, the solvent includes water, and the mass percentage of the secondary particles is 15%-30%, for example, the mass percentage of the secondary particles is 15%, 20%, 25% or 30%, or within the range of any two of the above values. The mass percentage of the emulsifier is 0.1%-2%, for example, the mass percentage of the emulsifier is 0.1%, 1.0%, 1.5% or 2%, or within the range of any two of the above values. Preferably, the mass percentage of the emulsifier is 0.1%-0.8%. Controlling the mass percentage of the emulsifier within the above range can avoid the formation of secondary particles due to excessive emulsifier, and can also effectively ensure the dispersion of the secondary particles in the solvent.

[0066] In some embodiments, mechanical stirring is used when mixing the solvent, emulsifier and secondary particles. The rotation speed of the mechanical stirring is 300rpm-600rpm, and the mixing time is 10min-30min. Controlling the stirring speed and mixing time can avoid affecting the shape retention of the secondary particles due to excessive speed, and can also ensure that the secondary particles are fully and evenly dispersed in the solvent.

[0067] S103 , mixing the solvent, the emulsifier and the monomers for preparing the coating layer 200 to prepare an emulsion for the coating layer 200 .

[0068] Specifically, in the preparation of the coating layer 200 emulsion, the mass percentage of the emulsifier is 0.1%-2%. For example, the mass percentage of the emulsifier is 0.1%, 1.0%, 1.5% or 2%, or in the range of any two of the above values. Controlling the mass percentage of the emulsifier within the above range can effectively ensure the dispersion of the coating layer 200 raw materials in the solvent.

[0069] S104, mixing the secondary particle emulsion, the coating layer 200 emulsion and the initiator, heating and reacting, so that the prepared monomers are polymerized on the surface of the secondary particles to form the coating layer 200, and porous polymer microspheres are prepared.

[0070] Specifically, the temperature of the heating reaction is 75°C-90°C. For example, the heating temperature is 75°C, 80°C, 85°C or 90°C, or a range of any two of the above values. When the secondary particle emulsion, the coating layer 200 emulsion and the initiator are mixed, the secondary particle emulsion and the initiator are first mixed, and then the coating layer 200 emulsion is added while stirring. After the addition is completed, the temperature is raised to the heating temperature, and then stirred for heating reaction. After the reaction is completed, the temperature is lowered to room temperature, and porous polymer microspheres or porous polymer microsphere emulsions can be obtained.

[0071] In some embodiments, see Figure 4 In order to further effectively ensure the drying of the porous polymer microspheres and facilitate their storage and subsequent configuration of the coating slurry, step S105 is also included: drying and dehydrating treatment is performed after the heating reaction to obtain dry porous polymer microspheres, and the drying and dehydrating treatment includes vacuum drying or spray drying.

[0072] The present application also provides a membrane coating slurry, comprising the above-mentioned porous polymer microspheres.

[0073] In some embodiments, in the membrane coating slurry, the mass percentage of porous polymer microspheres is 8%-20%. For example, the mass percentage of porous polymer microspheres is 8%, 10%, 12%, 18% or 20%, or in the range of any two of the above values. Preferably, the mass percentage of porous polymer microspheres is 10%-16%. Controlling the mass percentage of porous polymer microspheres can avoid the situation where the content of porous polymer microspheres is too low to meet the bonding requirements, and can also avoid the situation where the content of porous polymer microspheres is too high to affect the air permeability of the membrane.

[0074] In some embodiments, the solid content of the membrane coating slurry is 10%-20%. For example, the solid content of the membrane coating slurry is 10%, 12%, 15%, 18% or 20%, or a range consisting of any two of the above values.

[0075] In other embodiments, when preparing porous polymer microspheres, the undried porous polymer microsphere emulsion can be directly used to prepare the membrane coating slurry in step S104. By diluting the porous polymer microsphere emulsion to adjust the membrane coating slurry to meet the above-mentioned solid content requirements, the drying step and the heating reaction time can be saved, thereby improving production efficiency.

[0076] In some embodiments, the membrane coating slurry further comprises a wetting agent and an adhesive. Specifically, the adhesive may be a polyacrylate adhesive. Specifically, the wetting agent comprises at least one of fluoroalkyl methoxy ether alcohol, fluoroalkyl ethoxy ether alcohol, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, polyvinyl alcohol, fatty acid polyoxyethylene ether and polyoxyethylene.

[0077] In some embodiments, the mass percentage of the adhesive is 0.5%-2%. For example, the mass percentage of the adhesive is 0.5%, 0.8%, 1%, 1.5% or 2%, or a range of any two of the above values. The provision of the adhesive can improve the adhesion between the porous polymer microspheres, thereby improving the stability and mechanical strength of the diaphragm, and can also improve the coating effect between the diaphragm coating slurry and the diaphragm.

[0078] In some embodiments, the mass percentage of the wetting agent is 0.1%-0.8%. For example, the mass percentage of the wetting agent is 0.1%, 0.2%, 0.4%, 0.6% or 0.8%, or a range composed of any two of the above values. The provision of the wetting agent can improve the wetting effect between the diaphragm coating slurry and the diaphragm, thereby improving the uniformity and consistency of the diaphragm coating slurry coating.

[0079] The present application provides a membrane, comprising the above-mentioned porous polymer microspheres and a porous substrate. The porous polymer microspheres constitute a polymer coating, which can be coated on at least one surface of the porous substrate.

[0080] In some embodiments, the porous substrate is selected from at least one of a polyethylene film, a polypropylene film, a polyimide film, a polyvinylidene fluoride film, a polyvinylidene fluoride-hexafluoropropylene film, a polyamide film, and a polyethylene terephthalate film. The thickness of the porous substrate is 5 μm-25 μm. For example, the thickness of the porous substrate is 5 μm, 10 μm, 15 μm, 20 μm or 25 μm, or within the range of any two of the above values. If the porous substrate is too thick, the thinning of the diaphragm will be affected, and the energy density of the battery will be affected. If it is too small, the mechanical strength of the diaphragm will be affected. The porosity of the porous substrate is 30%-65%. For example, the porosity of the porous substrate is 30%, 35%, 40%, 45%, 50%, 55%, 60% or 65%, or within the range of any two of the above values. Controlling the porosity within the above range can effectively ensure the transmission of ions, thereby ensuring the cycle performance and service life of the battery.

[0081] In some embodiments, the polymer coating can be prepared by spray coating, roller coating, spot coating, dip coating, and the like.

[0082] In some embodiments, the thickness of the polymer coating is 1 μm-10 μm. For example, the thickness of the polymer coating is 1 μm, 2 μm, 5 μm, 7 μm or 10 μm, or in a range of any two of the above values. Preferably, it is 2 μm-5 μm. Controlling the thickness of the polymer coating can effectively avoid the coating being too thick to affect the performance of the diaphragm, and can also avoid the coating being too thin to achieve the desired bonding effect.

[0083] The present application also provides a secondary battery, comprising a battery separator prepared from the porous polymer microspheres.

[0084] The technical solution of the present application is further described below through specific embodiments.

[0085] Embodiment 1

[0086] Preparation of porous polymer microspheres: polyvinylidene fluoride homopolymer (PVDF) particles (average particle size 120nm, melting point 130°C) and surfactant are mixed in a mass ratio of 100:1, mechanically stirred for 30 minutes, and then dispersed in an aqueous solution containing 0.5wt% emulsifier, stirred at 500rpm for 15 minutes, polyvinylidene fluoride homopolymer (PVDF) particles aggregate to form secondary particles, and a 20wt% secondary particle emulsion is prepared. Among them, the particle size of the secondary particles is 1μm-10μm. Methyl methacrylate (MMA) is added to an aqueous solution containing 1wt% emulsifier, stirred at 500rpm for 1 hour, and a coating layer 200 emulsion with a monomer concentration of 50wt% is prepared. 0.5 wt% of water-soluble initiator was added to the secondary particle emulsion, and then the coating layer 200 emulsion (PVDF:PMMA mass ratio of 10:1) was added to the secondary particle emulsion while stirring. After the addition was completed, the temperature was raised to 80°C and stirred at 500 rpm for 30 minutes. After the reaction was completed, the temperature was lowered to room temperature to obtain a porous polymer microsphere emulsion.

[0087] Preparation of the diaphragm: The porous polymer microsphere emulsion was diluted with deionized water, and the adhesive was added in a ratio of 15:1 to obtain a coating slurry with a solid content of 16%. The coating slurry was double-sidedly rolled on the surface of a polypropylene porous membrane (thickness 12 μm, porosity 40%) and dried to obtain a diaphragm with a thickness of 16 μm.

[0088] The scanning electron microscope image of the diaphragm in this embodiment is as follows Figure 5 shown.

[0089] Embodiment 2

[0090] The difference between this embodiment and the first embodiment is that, in the preparation of the porous polymer microspheres, the obtained porous polymer microsphere emulsion is spray-dried to remove the solvent to obtain the porous polymer microspheres.

[0091] Preparation of the diaphragm: 15 parts by mass of porous polymer microspheres, 0.5 parts by mass of a wetting agent and 83.5 parts by mass of deionized water were stirred and mixed uniformly, and then 1 part by mass of an adhesive was added and stirred and mixed uniformly to obtain a coating slurry with a solid content of 16.5%. The coating slurry was double-sidedly rolled onto the surface of a polypropylene porous film (thickness 12 μm, porosity 40%) and dried to obtain a diaphragm with a thickness of 16 μm.

[0092] Embodiment 3

[0093] The difference between this embodiment and the second embodiment is that in the preparation of the porous polymer microspheres, the mass ratio of PVDF:PMMA is 2:1.

[0094] Embodiment 4

[0095] The difference between this embodiment and the second embodiment is that in the preparation of the porous polymer microspheres, the mass ratio of PVDF:PMMA is 5:1.

[0096] Embodiment 5

[0097] The difference between this embodiment and the second embodiment is that in the preparation of the porous polymer microspheres, the mass ratio of PVDF:PMMA is 20:1.

[0098] Comparative Example 1

[0099] The difference between this example and Example 2 is that in the preparation of the diaphragm, the porous polymer microspheres are replaced with polyvinylidene fluoride homopolymer (PVDF) particles (average particle size 120nm, melting point 130°C). The scanning electron microscope image of the diaphragm in this comparative example is as follows: Figure 6 shown.

[0100] Preparation of the diaphragm: 15 parts by mass of PVDF particles, 0.5 parts by mass of wetting agent and 83.5 parts by mass of deionized water were stirred and mixed uniformly, and then 1 part by mass of adhesive was added and stirred and mixed uniformly to obtain a coating slurry with a solid content of 16.5%. The coating slurry was coated on both sides of a polypropylene porous membrane (thickness 12 μm, porosity 40%), and dried to obtain a diaphragm with a thickness of 16 μm.

[0101] Comparative Example 2

[0102] The difference between this comparative example and comparative example 1 is that in the preparation of the diaphragm, part of the polyvinylidene fluoride homopolymer (PVDF) particles (average particle size 120 nm, melting point 130° C.) are replaced with polymethyl methacrylate (PMMA) microspheres (average particle size 500 nm).

[0103] Preparation of the diaphragm: 13.5 parts by mass of PVDF particles, 1.5 parts by mass of PMMA particles, 0.5 parts by mass of a wetting agent and 83.5 parts by mass of deionized water were stirred and mixed uniformly, and then 1 part by mass of an adhesive was added, and stirred and mixed uniformly to obtain a coating slurry with a solid content of 16.5%. The coating slurry was double-sidedly rolled on the surface of a polypropylene porous membrane (thickness 12 μm, porosity 40%), and dried to obtain a coating diaphragm, and the thickness of the coating diaphragm was 16 μm.

[0104] Comparative Example 3

[0105] The difference between this comparative example and Example 2 is that the preparation method of the polymer microspheres is different.

[0106] Preparation of polymer microspheres: Disperse polyvinylidene fluoride homopolymer (PVDF) particles (average particle size 120nm, melting point 130℃) in an aqueous solution containing 0.5wt% emulsifier, stir at 500rpm for 15 minutes to prepare a 20wt% polymer particle emulsion. Add methyl methacrylate (MMA) to an aqueous solution containing 1wt% emulsifier, stir at 500rpm for 1 hour, and prepare a 200 emulsion of the coating layer with a monomer concentration of 50wt%. Add 0.5wt% of water-soluble initiator to the polymer particle emulsion, and then add the coating layer 200 emulsion to the polymer particle emulsion while stirring (according to the PVDF:PMMA mass ratio of 10:1). After the addition is completed, heat to 80℃ and stir at 500rpm for 30min. After the reaction is completed, cool to room temperature to obtain a polymer microsphere emulsion with PVDF primary particles as the core.

[0107] The diaphragms of the above embodiments and comparative examples were tested. The test method is as follows:

[0108] 25℃ pole piece bonding strength test: the battery separator sample is cut into 20mm×100mm strips, and the positive electrode sheet is cut into 20mm×100mm as the base plate, and the test sample is made after cold pressing for 60s at 3MPa pressure and 25℃. Then the bonding strength between the separator and the pole piece is tested using a tensile tester.

[0109] 80℃ pole piece bonding strength test: The battery separator sample was cut into 20mm×100mm strips, and the positive electrode was cut into 20mm×100mm as the base plate. The test sample was made by hot pressing at 2MPa pressure and 80℃ for 60s. Then the bonding strength between the separator and the pole piece was tested using a tensile tester.

[0110] Test of the bonding strength between separators: The battery separator samples were cut into 20 mm × 100 mm strips and double-layered, and pressed for 60 seconds at 1 MPa and 25°C to make test samples. Then the bonding strength between the separators was tested using a tensile testing machine.

[0111] Diaphragm thickness test: measured by Mahr thickness gauge, unit is μm. Test reference GB / T6672-2001 "Mechanical measurement method for thickness of plastic film and sheet".

[0112] Test of liquid absorption rate: Cut 5 samples of 100*100mm in size, weigh the mass, immerse each sample in the electrolyte for 10 minutes, take out the sample, use filter paper to absorb the electrolyte on the surface, weigh the mass again, and calculate the percentage of mass increase after immersion in the electrolyte, which is the liquid absorption rate. The average value of the liquid absorption rate of the 5 samples is its liquid absorption rate.

[0113] The membrane compositions and test results of Examples 1 to 5 and Comparative Examples 1 to 3 are shown in Table 1 below.

[0114] Table 1

[0115]

[0116]

[0117] From the data in Table 1, it can be seen that the PVDF coated diaphragm prepared in Comparative Example 1 cannot bond to the positive electrode under room temperature pressing and has poor liquid absorption capacity. Figure 5 and Figure 6 It can also be compared from the scanning electron microscope image of the diaphragm that the agglomerated structures of multiple PVDFs in the diaphragm prepared in comparative example 1 are uneven in size, and the porosity is not as good as that in example one, which further confirms that the liquid absorption performance and compression performance of comparative example 1 are worse than those of the example. Comparative example 2 uses a mixed coating of PVDF particles and PMMA particles, and the room temperature electrode adhesion and liquid absorption rate are slightly improved compared with comparative example 1. The diaphragms prepared by porous polymer microspheres of Examples 1 to 5 of this scheme have good electrode adhesion and high liquid absorption rate under room temperature pressing, which are significantly improved compared with comparative examples 1 and 2. Comparative example 3 directly uses PVDF particles to prepare an emulsion and reacts with the coating layer 200 emulsion to prepare polymer particles with a core-shell structure to make a diaphragm coating. Compared with example one, its liquid absorption rate is poor, and the bonding strength at room temperature is worse than that of example one, and the thickness of comparative example three after pressing is greater than that of example one, and its compression rate is worse than that of example one, so the effect of improving the battery energy density is worse than that of example one.

[0118] The above specific examples are used to illustrate the present application, which is only used to help understand the present application and is not intended to limit the present application. For technicians in the technical field to which the present application belongs, they can also make some simple deductions, deformations or substitutions based on the ideas of the present application.

Claims

1. A porous polymer microsphere, characterized in that: The porous polymer microsphere has a porous structure inside, including secondary particles and a coating layer coated on the surface of the secondary particles. The secondary particles are a porous grid structure formed by polymerization of primary particles. The primary particles include polyvinylidene fluoride polymers, and the coating layer includes polyacrylic acid polymers.

2. The porous polymer microsphere according to claim 1, characterized in that: The coating layer is discontinuously coated on the surface of the secondary particles.

3. The porous polymer microsphere according to claim 1, characterized in that: The coating layer continuously coats the surface of the secondary particles.

4. The porous polymer microsphere according to any one of claims 1 to 3, characterized in that The porous polymer microspheres satisfy at least one of the conditions (1) to (6): (1) The particle size of the porous polymer microspheres is 1 μm-10 μm; (2) In the porous polymer microspheres, the mass ratio of the polyvinylidene fluoride polymer to the polyacrylic acid polymer is 2:1-20:1; (3) The polyvinylidene fluoride polymer includes at least one of a polyvinylidene fluoride homopolymer, a polyvinylidene fluoride-trifluoroethylene copolymer and a polyvinylidene fluoride-hexafluoropropylene copolymer; (4) The melting point of the polyvinylidene fluoride polymer is 80°C-150°C; (5) The particle size of the primary particles is 80nm-400nm; (6) The polyacrylic acid polymer includes a polymer composed of at least one monomer selected from the group consisting of acrylic acid, acrylic ester, acrylonitrile and acrylamide; optionally, the polyacrylic acid polymer is polymethyl methacrylate.

5. A method for preparing porous polymer microspheres, wherein the porous polymer microspheres are the porous polymer microspheres according to any one of claims 1 to 4, characterized in that: The steps include: The primary particles are mixed with a surfactant to prepare secondary particles having a porous grid structure; Mixing a solvent, an emulsifier and the secondary particles to form a secondary particle emulsion; Mixing a solvent, an emulsifier and a monomer for preparing a coating layer to form a coating layer emulsion; The secondary particle emulsion, the coating layer emulsion and the initiator are mixed and heated for reaction, so that the prepared monomers are polymerized on the surface of the secondary particles to form the coating layer, thereby preparing porous polymer microspheres.

6. The method for preparing porous polymer microspheres according to claim 5, characterized in that: When preparing the porous polymer microspheres, at least one of the conditions (1) to (5) is met: (1) The surfactant comprises at least one of fluoroalkyl methoxy ether alcohol, fluoroalkyl ethoxy ether alcohol, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, polyvinyl alcohol, fatty acid polyoxyethylene ether and polyoxyethylene; (2) In the step of preparing the secondary particles, the mass ratio of the primary particles to the surfactant is 100:0.1-100:2; (3) In the secondary particle emulsion, the mass percentage of the secondary particles is 15%-30%; the mass percentage of the emulsifier is 0.1%-2%; (4) In the coating layer emulsion, the mass percentage of the emulsifier is 0.1%-2%; (5) The temperature of the heating reaction is 75°C-90°C.

7. The method for preparing porous polymer microspheres according to claim 5 or 6, characterized in that: The method further comprises performing a drying and dehydration treatment after the heating reaction to obtain dry porous polymer microspheres, wherein the drying and dehydration treatment comprises vacuum drying or spray drying.

8. A diaphragm coating slurry, characterized in that: The porous polymer microsphere comprises the porous polymer microsphere as described in any one of claims 1 to 4 or the porous polymer microsphere prepared by the preparation method as described in any one of claims 5 to 7.

9. The diaphragm coating slurry according to claim 8, characterized in that: The membrane coating slurry satisfies at least one of the conditions (1)-(2): (1) In the membrane coating slurry, the mass percentage of the porous polymer microspheres is 8%-20%; (2) The solid content of the diaphragm coating slurry is 10%-20%.

10. A diaphragm, characterized in that: The porous polymer microspheres include those described in any one of 1 to 4 or those prepared by the preparation method described in any one of claims 5 to 7.

Citation Information

Cited By

  • Diaphragm coating material capable of being quickly bonded with pole piece as well as preparation method and application of diaphragm coating material

    CN120657373A